Multilingual News–An Investigation of Consumption, Querying, and Search Result Selection Behaviors. Issue 6 (2nd April 2020) - Ling, Chenjun; Steichen, Ben; Figueira, Silvia
ABSTRACT: With the global expansion of the Internet and the World Wide Web, users are becoming increasingly diverse, particularly in terms of languages. In fact, there are now many users online who are polyglots, i.e. users who are proficient in more than one language. However, even such multilingual users often continue to suffer from unbalanced and fragmented news information, as traditional news access systems seldom allow users to simultaneously search for and/or compare news in different languages, even though prior research results have shown that multilingual users make significant use of each of their languages when generally searching for information online. The research presented in this paper provides the first investigation of multilingual news consumption, as well as a detailed analysis of multilingual querying and search result selection behaviors. In particular, through a set of 2 phases of crowdsourced user studies, this paper presents the first human-centered studies in multilingual news access, aiming to drive the development of personalized multilingual news access systems that better support each individual user.